Care for Critically Ill Patients with Incontinence-Associated Dermatitis: A Case Study - Khanantai, Chanon; Wetsom, Patcharin (Vajira Nursing Journal, 2024)
Incontinence-associated dermatitis (IAD) is a leading cause of pressure injury and negatively impacts the achievement of key performance indicators in critical care units. This article aims to present: 1) risk factors for the development of IAD, 2) the mechanisms of IAD formation, 3) risk assessment tools and severity assessment tools for IAD 4) prevention and management of IAD based on severity levels. Results of care showing the integration of IAD prevention and management cycle framework along with evidence-based practices in critically ill patients with IAD that effectively reduce IAD severity and promote IAD healing.